2022
DOI: 10.3390/ijerph19074311
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Sleepiness Measured by Diaries and Actigraphy among Norwegian and Austrian Helicopter Emergency Medical Service (HEMS) Pilots

Abstract: The study examined sleep and sleepiness among shift working Helicopter Emergency Medical Service pilots from Norway (Norwegian Air Ambulance; NAA) and Austria (Christophorus Flugrettungverein; CFV). Both pilot groups (N = 47) worked seven consecutive 24 h shifts. Sleep was assessed by diaries and actigraphy while sleepiness was assessed by the Karolinska Sleepiness Scale, all administered throughout the workweek. The results indicated that all pilots had later bedtime (p < 0.05) and wake-up time (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Other studies have reported similar sleepiness dynamics. A study of sleepiness dynamics in helicopter pilots showed a steady increase in subjective sleepiness after 8:00 p.m. (KSS) [13]. The level of subjective sleepiness in fishermen of different vessel types increased towards the evening [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported similar sleepiness dynamics. A study of sleepiness dynamics in helicopter pilots showed a steady increase in subjective sleepiness after 8:00 p.m. (KSS) [13]. The level of subjective sleepiness in fishermen of different vessel types increased towards the evening [3].…”
Section: Discussionmentioning
confidence: 99%
“…Night 2 of 14 shifts have been shown to result in decreased productivity, manifested by increased reaction time [1] and an increase in serious errors [3]. Similar trends persist across different professions: helicopter pilots [13], fishermen [3], healthcare workers [2,11], and metallurgists [1]. Subjective vigilance and neurobehavioral indicators are also impaired in simulated night shift conditions [14].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation